Impact of merger and acquisition announcements on stock return, volatility and liquidity of acquirers: evidence from the Indian banking sector / Pinky Mal and Kapil Gupta - Mal, Pinky; Gupta, Kapil (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2020)
This study attempts to examine the stock behaviour of acquirer banks during pre and post-merger and acquisition (M&A) announcement period in the Indian banking sector. Data of M&A events that took place in the Indian banking sector during 2000-2018 was collected from the prowessdx database. The sample consisted of 31 merger and 351 acquisition announcements during 2000-2018 in the Indian Banking sector. Stock prices of sample banks were extracted from the NSE for an event window of -10 to +10 days and the event study methodology was used for analysis. The results suggest that shareholders of Indian acquirer banks generate small and insignificant abnormal returns from M&A deals. Return variability was also noticed from the curvy jumps in the average abnormal spread of returns during the announcement period. Whereas, the average abnormal change in liquidity witnessed a sharp hike on day 0 i.e. the date of deal announcement and it remained negative throughout the post-deal period.